Evaluating the Implementation of Learning Management System: The Case of an English Education Study Program - Astawa, Ni Luh Putu Ning Septyarini Putri; Adiwijaya, Pande Agus (Universitas Jambi, Indonesia, 2024)
E-learning is an application of information technology in education. Students could communicate at any time and location because digital learning resources were distributed and accessible via the network. This research was to investigate the extent to which students are prepared to participate in e-learning. The research methodology employed was descriptive quantitative. The research sample consisted of 62 students of the English Education Study Program ITP Markandeya Bali. Students answered 27 points of questionnaires based on evaluation models Context, Input, Process, and Product (CIPP). The distribution of data acquisition was repeated to ensure data consistency. Students’ readiness to participate in e-learning was measured using the CIPP model, with the following results: (1) Context aspects of 84.675% (High), (2) Input aspects of 83.86% (High), (3) Process aspects of 90.6% (Very High), and (4) Product aspects of 91.4% (Very High). Some recommendations are added to this research.